Effects of the driving context on the usage of Automated Driver Assistance Systems (ADAS) -Naturalistic Driving Study for ADAS evaluation. (March 2020) - Orlovska, Julia; Novakazi, Fjollë; Lars-Ola, Bligård; Karlsson, MariAnne; Wickman, Casper; Söderberg, Rikard
Abstract: Automated Driver Assistance Systems (ADAS) are designed to support the driver and enhance the driving experience. Due to ADAS limitations associated with the driving context, the intended use of ADAS functions is often non-transparent for the end-user. The system performance capabilities affected by the continuously changing driving context influence ADAS usage. However, the cumulative effect of the driving context on driver behavior and ADAS usage is insufficiently covered in the ongoing research. This paper aims to investigate and understand how the driving context affects the use of ADAS. Throughout this research, data from a Naturalistic Driving (ND) study was collected and analyzed. The analysis of the ND data helped to register how drivers use ADAS in different driving conditions and indicated several issues associated with ADAS usage. To be able to clarify the outcomes of quantitative sensor-based data analysis, an explanatory sequential mixed-method design was implemented. The method facilitated the subsequent design of qualitative in-depth interviews with the drivers. The combined data analysis allowed a holistic interpretation and evaluation of the findings regarding the effect of the driving context on ADAS usage. The findings warrant consideration of the driving context as a key factor enabling the effective development of ADAS functions. Highlights: This paper presents interdisciplinary research combining quantitative and qualitative approaches. We investigated how the driving context affects the use of Automated Driver Assistance Systems (ADAS). The study is based on Volvo Naturalistic Driving data of 132 vehicles collected for the time period of seven months. We identified the threefold interrelation including driver behavior, system performance, and driving context. We stressed the importance of the driving context parameters in the design, development and evaluation of ADAS.